Indonesia : Technical Assistance Report-Report on Sectoral Financial Accounts and Balance Sheets Technical Assistance Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
As part of the Switzerland State Secretariat for Economic Affairs (SECO) project, a technical assistance mission visited Jakarta, Indonesia, during January 8-12, 2018, to develop the capacity to compile integrated sectoral accounts and balance sheets data. The mission reviewed the results of the work undertaken to implement the recommendations of the September 2017 mission.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet